Quarkyonic equation of state with momentum-dependent interaction and neutron star structure - Folias, Konstantinos; Moustakidis, Charalambos (HNPS Advances in Nuclear Physics, 2025)
The structure and basic properties of dense nuclear matter still remain one of the open problems of physics. In particular, the composition of the matter that composes neutron stars is under theoretical and experimental investigation. Among the theories that have been proposed, apart from the classical one where the composition is dominated by hadrons, the existence or coexistence of free quark matter is a dominant guess. An approach towards this solution is the phenomenological view according to which the existence of quarkyonic matter plays a dominant role in the construction of the equation of state (EOS). In this paper we propose a phenomenological model for quarkyonic matter, borrowed from corresponding applications in hadronic models, where the interaction in the quarkyonic matter depends not only on the position but also on the momentum of the quarkynions. This consideration, as we demonstrate, can have a dramatic consequence on the shape of the EOS and thus on the properties of neutron stars.